Ordinance no. 26, § 6, DALLES CITY, CHARTER & GENERAL ORDINANCES (Himes the Printer 1882). - (:unkn) unknown (General Publisher, 1881)
Shooting galleries shall pay a quarterly license of five dollars. Every place or building where guns or pistols are kept for shooting at targets, whether for hire or not, shall be deemed a shooting gallery under this ordinance.
--
Keywords: SHOOTING RANGES OR GALLERIES